PENGARUH VARIASI JENIS LIMBAH SAYURAN (KUBIS, SAWI, SELADA) DAN KADAR EM4 PADA PEMBUATAN PUPUK KOMPOS DENGAN PROSES FERMENTASI - anita; Setyawati, Harimbi; Sari, Sanny Andjar; Nathania, Devona; Zahwa, Nadila (Teknik Kimia ITN Malang, 2021)
Traditional markets produce solid vegetable waste every day, including cabbage, mustard greens and lettuce as well as other vegetables in large quantities. Therefore, a proper technology needs to be applied to deal with the solid vegetable waste. The technology is the recycling technology, that is converting vegetable waste into compost which has more selling value and high use value as natural plant fertilizer without any chemicals. This study aims to determine the effect of various types of vegetable waste and levels of EM4 on composting by the fermentation process. The variables used were EM4 levels 2%, 3%, 4%, 5%, and 6% and the types of the solid vegetable waste used were cabbage, mustard, and lettuce vegetable waste. These materials were put into polybags. The anaerobic fermentation was carried out for 14 days, which every two days was checked for the temperature and pH level. The best analysis results for nitrogen content were obtained in the variety of mustard solid waste with a concentration of EM4 6%, which was 1.06%. The highest phosphorus content was found in the variety of cabbage solid waste with 5% EM4 concentration, which was 0.3%. while the highest potassium content was found in the variety of cabbage solid waste with EM4 concentration of 4%, which was 2.12%